Efficacy of third-line anti-EGFR-based treatment versus regorafenib or trifluridine/tipiracil according to primary tumor site in RAS/BRAF wild-type metastatic colorectal cancer patients - Salvatore, Lisa; Bensi, Maria; Vivolo, Raffaella; Zurlo, Ina Valeria; Dell’Aquila, Emanuela; Grande, Roberta; Anghelone, Annunziato; Emiliani, Alessandra; Citarella, Fabrizio; Calegari, Maria Alessandra; Ribelli, Marta; Basso, Michele; et al. (Frontiers in Oncology, 2023)
Background: Right- (R) and left-sided (L) metastatic colorectal cancer (mCRC) exhibit different clinical and molecular features. Several retrospective analyses showed that survival benefit of anti-EGFR-based therapy is limited to RAS/BRAF wt L-sided mCRC patients. Few data are available about third-line anti-EGFR efficacy according to primary tumor site. Methods: RAS/BRAF wt patients mCRC treated with third-line anti-EGFR-based therapy versus regorafenib or trifluridine/tipiracil (R/T) were retrospectively collected. The objective of the analysis was to compare treatment efficacy according to tumor site. The primary endpoint was progression-free survival (PFS); secondary endpoints were overall survival (OS), response rate (RR) and toxicity. Results: A total of 76 RAS/BRAF wt mCRC patients, treated with third-line anti-EGFR-based therapy or R/T, were enrolled. Of those, 19 (25%) patients had a R-sided tumor (9 patients received anti-EGFR treatment and 10 patients R/T) and 57 (75%) patients had a L-sided tumor (30 patients received anti-EGFR treatment and 27 patients R/T). A significant PFS [7.2 vs 3.6 months, HR 0.43 (95% CI 0.2-0.76), p= 0.004] and OS benefit [14.9 vs 10.9 months, HR 0.52 (95% CI 0.28-0.98), p= 0.045] in favor of anti-EGFR therapy vs R/T was observed in the L-sided tumor group. No difference in PFS and OS was observed in the R-sided tumor group. A significant interaction according to primary tumor site and third-line regimen was observed for PFS (p= 0.05). RR was significantly higher in L-sided patients treated with anti-EGFR vs R/T (43% vs. 0%; p <0.0001), no difference was observed in R-sided patients. At the multivariate analysis, third-line regimen was independently associated with PFS in L-sided patients. Conclusions: Our results demonstrated a different benefit from third-line anti-EGFR-based therapy according to primary tumor site, confirming the role of L-sided tumor in predicting benefit from third-line anti-EGFR vs R/T. At the same time, no difference was observed in R-sided tumor.